2016
DOI: 10.3390/ijms17040442
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Carbon Monoxide (CO) Produced by Heme Oxygenases and Derived from the CO-Releasing Molecule CORM-2 in the Pathogenesis of Stress-Induced Gastric Lesions: Evidence for Non-Involvement of Nitric Oxide (NO)

Abstract: Carbon monoxide (CO) produced by heme oxygenase (HO)-1 and HO-2 or released from the CO-donor, tricarbonyldichlororuthenium (II) dimer (CORM-2) causes vasodilation, with unknown efficacy against stress-induced gastric lesions. We studied whether pretreatment with CORM-2 (0.1–10 mg/kg oral gavage (i.g.)), RuCl3 (1 mg/kg i.g.), zinc protoporphyrin IX (ZnPP) (10 mg/kg intraperitoneally (i.p.)), hemin (1–10 mg/kg i.g.) and CORM-2 (1 mg/kg i.g.) combined with NG-nitro-l-arginine (l-NNA, 20 mg/kg i.p.), 1H-[1,2,4]ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…Moreover, the upregulation of gastric mucosal iNOS protein expression induced by aspirin was decreased in rats pretreated with CORM-2 but not with NaHS. This finding is in keeping with our previous observation that CO released from CORM-2 decreased NO content that was possibly elevated because of an increase in iNOS activity in gastric mucosa of rats compromised by stress and that L-NNA had no effect on the gastroprotective action of this compound [26]. Regarding the effect of L-NNA on NaHS-induced gastroprotection, there is convincing evidence that H 2 S can interact with NO in the regulation of mucus secretion, GBF, and gastric mucosal defense in experimental models and in regulation of vascular tone in animals and humans [36,37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the upregulation of gastric mucosal iNOS protein expression induced by aspirin was decreased in rats pretreated with CORM-2 but not with NaHS. This finding is in keeping with our previous observation that CO released from CORM-2 decreased NO content that was possibly elevated because of an increase in iNOS activity in gastric mucosa of rats compromised by stress and that L-NNA had no effect on the gastroprotective action of this compound [26]. Regarding the effect of L-NNA on NaHS-induced gastroprotection, there is convincing evidence that H 2 S can interact with NO in the regulation of mucus secretion, GBF, and gastric mucosal defense in experimental models and in regulation of vascular tone in animals and humans [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have documented that the mechanism of aspirin-induced gastric damage involves an inhibition of cytoprotective prostaglandin E 2 production via COX-1/ COX-2 enzymatic activity and the prominent fall in GBF leading to the formation of severe hemorrhagic lesions of gastric mucosa [5,[29][30][31][32][33]. On the other hand, recent studies reported that the endogenous gaseous mediators H 2 S, CO, and NO contribute to the maintenance of gastric mucosal integrity and prevent the formation of gastric mucosal lesions induced by various noxious stimuli, such as exposure to stress or administration of ethanol, bisphosphonates, and NSAIDs, including aspirin [5,17,19,21,22,26,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One day after the induction of a gastric ulcer, animals were randomly divided into appropriate experimental groups consisting of five animals in each ( n = 5) and were treated daily, intragastrically (i.g. ), throughout the period of 9 days with (i) vehicle (saline or DMSO/saline solution 1/10); (ii) CORM‐2 (0.1–10 mg·kg −1 ); (iii) RuCl 3 (2.5 mg·kg −1 ), as a negative control for CORM‐2, which does not release CO (Takasuka et al ., ; Magierowska et al ., ); (iv) haemin, an HO1 inducer (Park et al ., ; Magierowska et al ., ), at a dose of 5 mg·kg −1 , which has been previously reported to protect the gastric mucosa against ethanol‐induced damage (Magierowska et al ., ); and (v) ZnPP, an HOs inhibitor (Hirai et al ., ), at a dose of 10 mg·kg −1 , previously reported to decrease CO content in gastric mucosa (Magierowska et al ., ). In the majority of experiments, CORM‐2 was administered at a dose of 2.5 mg·kg −1 , which decreased the ulcer area by more than 50% compared with the vehicle control group.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of mRNA for EGF, HO1, HO2, COX‐2, iNOS, HIF‐1α, TNF‐α, IL‐1β and β‐actin (as housekeeping gene) in gastric mucosa was determined by semi‐quantitative real‐time PCR, as described previously (Magierowska et al ., ; ). Briefly, RNA was isolated from gastric mucosal samples using GeneMATRIX Universal RNA Purification Kit (EURx, Gdansk, Poland).…”
Section: Methodsmentioning
confidence: 99%